6(2n+1)=6(8n+5)+7

Simple and best practice solution for 6(2n+1)=6(8n+5)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2n+1)=6(8n+5)+7 equation:


Simplifying
6(2n + 1) = 6(8n + 5) + 7

Reorder the terms:
6(1 + 2n) = 6(8n + 5) + 7
(1 * 6 + 2n * 6) = 6(8n + 5) + 7
(6 + 12n) = 6(8n + 5) + 7

Reorder the terms:
6 + 12n = 6(5 + 8n) + 7
6 + 12n = (5 * 6 + 8n * 6) + 7
6 + 12n = (30 + 48n) + 7

Reorder the terms:
6 + 12n = 30 + 7 + 48n

Combine like terms: 30 + 7 = 37
6 + 12n = 37 + 48n

Solving
6 + 12n = 37 + 48n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-48n' to each side of the equation.
6 + 12n + -48n = 37 + 48n + -48n

Combine like terms: 12n + -48n = -36n
6 + -36n = 37 + 48n + -48n

Combine like terms: 48n + -48n = 0
6 + -36n = 37 + 0
6 + -36n = 37

Add '-6' to each side of the equation.
6 + -6 + -36n = 37 + -6

Combine like terms: 6 + -6 = 0
0 + -36n = 37 + -6
-36n = 37 + -6

Combine like terms: 37 + -6 = 31
-36n = 31

Divide each side by '-36'.
n = -0.8611111111

Simplifying
n = -0.8611111111

See similar equations:

| 2y-5=-20 | | -3p+2p= | | 5y^2=-7y-2 | | -2x=-3x^3-2 | | -5x+7x+16=11x-3-x | | x^3-5x+2x^2-10=0 | | 180-(7x-12)=5x | | -2(3t-4)+3t=5t-7 | | x+120=40 | | 5y+9=-2y+3 | | x-4y=y^2+7 | | 2y-5x=-20 | | 7x=-4x-3 | | 4y-11+5= | | -5(2t-3)+8t=7t-5 | | 7x-(7x-2)= | | 80x=3000 | | 52=(2w-5)w | | m-3x=2x-p | | 180-x=112 | | 1+-18=23.9 | | 2-3x=-34 | | 102v+16v= | | 8(4)=v(10) | | -2(5t-5)+7t=4t-8 | | 8-c=-13 | | p^3-2p+2p^3= | | 2x+3y=154 | | 2(1+4n)=-10+4n | | 2ln(5-x)=7 | | 180-(6x+4)=5x | | 4y-4-3= |

Equations solver categories